Romance languages and EFL: friends or foes? A study on the effects of romance intercomprehension training on plurilingual competence and EFL reading skills in young learners - Arenare, Giovanna; Carrasco Perea, Encarnación; López Ferrero, Carmen (International journal of multilingualism, 2024)
This article focuses on the effects of a 21-hour Romance Intercomprehension (RIC) module on the plurilingual competence in Romance languages of no prior knowledge and EFL reading comprehension skills of a group of Italian schoolchildren aged 10-11. Data were collected pre- and post-training through a simple language identification and comprehension questionnaire (within subjects, n = 19), and an EFL reading comprehension test (between subjects, RIC group n = 15; control n = 23), to answer the following questions: 1) What type of plurilingual reading strategies and competence can a short RIC module develop in a school con-text? and 2) Do the competences and strategies acquired through such a RIC course affect proficiency in EFL reading comprehension? Comparisons of pre- and post-test results indicated not only that the RIC-trained group did develop an initial level of plurilingual competence in Romance languages, but also that their EFL reading comprehension skills improved more than those of the control group. Further research is needed to substantiate these data and confirm this strategy transfer. However, alongside validating Intercomprehension methodology for quick development of plurilingual reading competence, this study seems to indicate that such competence can be extended outside a language family even in young learners.